New record of Gelotia Thorell, 1890 and a new species of Parahelpis Gardzińska & Żabka, 2010 (Araneae: Salticidae) from Australia - Patoleta, Barbara M.; Żabka, Marek (Zootaxa, 2020)
Gelotia robusta Wanless, 1984 (♂♀) and Parahelpis wandae sp. nov. (♂) from Northeast Queensland are diagnosed, described and illustrated. The genus Gelotia Thorell, 1890 is newly recorded from Australia, and the female of G. robusta is described for the first time. Distributional maps of the studied species are presented, and remarks on their relationships and distribution are provided.